Anti-Nuclear Movement in India: Protests in Kudankulam and Jaitapur. (February 2022) - Khan, Ajmal
This article discusses two prominent protest movements in India responding to nuclear energy expansion, protests related to the Kudankulam Nuclear Power Project in Tamil Nadu and the Jaitapur Nuclear Power Project in Maharashtra. Partly based on ethnographic fieldwork at both sites, the article argues that these protest movements are substantially different from anti-nuclear mobilisations outside South Asia. Indian nuclear-related protest movements problematise the tensions of development and environment from a grassroots perspective but struggle with opposing claims that more energy is needed. Locally, project-affected people do not trust government agencies to protect them and the local environment against creeping pollutions and potential disasters. Above all, local grievances are directed against high-handed procedures of compensating project-affected persons. Seen from this angle, these protest movements are in effect contributing to the arduous process of democratisation of governance regarding the constantly changing modalities of expanding energy provisions in India.